Scrotal insulation impairs spermatogenesis but not Sertoli cell endocrine function - Papa, Frederico Ozanam [UNESP]; Cavalero, Thais Mendes Sanches [UNESP]; Tironi, Stella Maris Teobaldo [UNESP]; Canuto, Lucas Emanuel Ferreira [UNESP]; Frasson, Mariana Silva [UNESP]; de Paula Freitas-Dell'Aqua, Camila [UNESP]; Conley, Alan James (Elsevier, 2023)
Testicular thermal insult is detrimental to spermatogenesis and a common cause of testicular degeneration. Changes in semen quality after scrotal insulation are well understood but its effects on Sertoli cell function is still not fully characterized. Isoform-specific assays have provided opportunities for analysis of inhibin-A and B. Recent studies in stallions have shown inhibin-B decreases after treatment with a GnRH receptor antagonist but returns with spermatogenesis after treatment stops, suggesting it may be a useful biomarker for testicular damage and recovery (Ball.et.al. Theriogenology; 2019; 213:108-115). The hypothesis of the present study was that serum inhibin-B correlates positively with sperm parameters after scrotal insulation decreasing as sperm motility and production decline. Stallions were assigned to a untreated control (n=4) and treated group (n=5) that was submitted to scrotal insulation for 1 hour in the morning and 1 hour in the afternoon, for two consecutive days, using a thermal blanket surrounding the scrotum. The intratesticular temperature was measured immediately after the blanket was removed and increased ∼10°C during the insulation period. Semen was collected twice weekly, but semen and serum samples were evaluated weekly for 98 days after treatment. Testicular response was assessed by determination of the concentrations of testosterone and estrone sulphate (interstitial compartment) and inhibin-B (tubular compartment), respectively. Spermkinetics were analyzed by CASA (IVOS Version 12 Hamilton Thorne Research, MA, USA), sperm concentration by Neubauer hemocytometer (Optik Labor®, Lancing, England), serum concentrations of inhibin- B and estrone sulfate were determined by ELISA and testosterone by RIA. Data were analyzed by ANOVA for repeated measures. Sperm motility and total sperm number decreased from day 4 to 67 (P<0.05) and sperm abnormalities increased from day 17 and did not recover until the end of our evaluation (day 98). Testosterone concentrations declined acutely. A significantly reduction in circulating testosterone concentrations occurred at 4, 9 and 37 days after onset of scrotal insulation, which is probably the result of Leydig cell impairment. However, no changes in inhibin-B or estrone sulfate were seen in response to treatment (n.s.). In , thermal insult appears to affect germ cells, and Leydig cell but not Sertoli cell function and, consequently, does not disturb inhibin-B synthesis. It has to be concluded that inhibin-B is no reliable biomarker for testicular damage and recovery from thermal insults. Acknowledgements: Authors are grateful to São Paulo Research Foundation (FAPESP, grant #2019/01119-8 and #2022/03405-0), the John P. Hughes Endowment and the Clinical Endocrinology Laboratory, University of California-Davis.